Cuisine as an emanation of National culturе (Philology, 2019)
The cultural lexicon is the most versatile part of the vocabulary. For this reason culinary terms almost never come within the Swadesh list, which contains the most stable word layer. Food-connected words reflect the livelihood activity, ethnic interactions, religious faiths and cultural area of peoples. The linguistic analysis testifies that for countries from the Persian cultural area the best-loved food is associated with braising, while for Englishmen and French this is meat. It is the Eastern-Orthodox doctrine that configures the semantic evolution of Bulgarian blazhen from ‘blissful’ to ‘impure, greasy’.
Keywords: history; cultural area; religious regulations; national cuisine; connotation; association area